Abnormal hemoglobin genotypes and ABO and rhesus blood groups associated with HIV infection among HIV-exposed infants in North Western Nigeria - Buseri FI; Okonkwo CN (Dove Medical Press, 2014)
Fiekumo I Buseri,1 Charity N Okonkwo21Hematology and Blood Transfusion Science Unit, Department of Medical Laboratory Science, Niger Delta University, Wilberforce Island, Bayelsa State, Nigeria; 2Department of Medical Laboratory Sciences, Rivers State University of Science and Technology, Port Harcourt, NigeriaBackground: Hemoglobin genotypes and blood groups have been known to be associated with diseases, but the relationship with human immunodeficiency virus (HIV) infection among Nigerian infants is not well known.Objective: This study aims to determine the association between hemoglobin genotypes and blood groups with HIV infection among HIV-exposed Nigerian infants.Methods: This cross-sectional study examined 312 HIV-exposed infants (aged 8–16 months) in Sokoto State, Nigeria. HIV screening was performed using the HIV DNA polymerase chain reaction technique on dried blood spots. Hemoglobin electrophoresis and ABO and Rhesus (Rh) blood groups were carried out using standard techniques.Results: This study found 20.5% HIV-1 seropositivity among the infants, with 20.9% of males and 20.1% of females positive for HIV-1. Babies' sex and HIV seropositivity was not significant (χ2=0.27, df=1, P=0.869). The blood group distribution was O (43.3%), A (36.8%), B (15.7%), AB (4.2%), RhD+ (95.6%), and RhD– (4.4%). The combined ABO and Rh blood groups among the study population were O+ (40.1%), A+ (36.2%), B+ (15.1%), AB+ (4.2%), O– (3.2%), A– (0.6%), and B– (0.6%). No AB– baby was found. The association between blood groups and HIV seropositivity was not significant (Fisher’s exact test =9.140; P=0.169); however, group AB+ showed the highest probable association with HIV seropositivity (46.2%), followed by A+ (23.9%). The prevalence of hemoglobin genotypes was AA (71.5%), AS (25.3%), AC (2.2%), and SC (1.0%). Hemoglobin SS and other hemoglobin variants were not found. A significant association (χ2=8.432, df=3, P=0.034) was observed between SC and HIV-1 infection, but not with ABO and Rh blood groups.Conclusion: Hemoglobin variant SC showed a significant association with HIV-1 infection, but not with ABO and Rh blood groups. Further studies are recommended to confirm this finding.Keywords: hemoglobin, blood groups, HIV, infants, Nigeria